v.2 - Sinha, R. K. (ed.) (New Delhi, 1989)
This Volume Two studies the techniques of economic planning and development. The type of growth models and the choice of techniques relevant for Indian conditions has always been debated ever since adoption of planning in India. The essays included in the volume have dealt at length the debate which is still continuing.
Keywords: Balance economic-India